Comunidades Virtuales de Aprendizaje: Una experiencia en el Área de Ingles - Fajardo-Murillo, Ruth Carmita; García-Herrera, Darwin Gabriel (Revista Arbitrada Interdisciplinaria Koinonía, 2021)
The purpose of this study is to address the study of the influence of the virtual learning community implemented by teachers from two educational institutions: the "Gabriela Mistral" General Basic Education School in the city of Cuenca, Ecuador and Tessa International School in Hoboken, New Jersey in the United States in the teaching of a Foreign Language, for the strengthening of oral expression in a second language. The methodology was based on a research with a mixed approach. For the quantitative, the result is that learning improved due to the interaction that was facilitated by the application of the different digital tools, and for the qualitative, the experience has allowed the children to know beyond their normal environment, they have been able to have contact with other cultures, learn new words that now use them and above all has aroused curiosity to know other countries.